Manajemen Risiko Usahatani Tembakau Kasturi Menghadapi Kondisi Perubahan Iklim (Studi Kasusu Kelompok Tani “ Surya Tani” Desa Sumberpinang Kecamatan Pakusari Kabupaten Jember) - Moh. Samsul Arifin; Ratih Apri Utami; Izza Orvala; Brian Nurmahadi (Jurnal Ekonomi Pertanian dan Agribisnis, 2023)
The purpose of this study was to determine the risk management applied by the farmer group "Surya Tani" Sumberpinang Village, Pakusari District, Jember Regency in the face of climate change. This research will be conducted on the farmer group "Surya Tani" Sumberpinang Village, Pakusari District, Jember Regency. Farmers who are members of the farmer group are affected by climate change which makes their tobacco crops fail to harvest. Damaged and wilted tobacco leaves are triggered by high soil moisture due to continuous rain during the dry season. This study uses a qualitative method with a descriptive research type. In addition, the data collection techniques used interviews, observation and documentation. This study concludes that 1) The income in tobacco cultivation is quite large and the multiple effects or impacts on the environment and surrounding social life are also quite significant. Farmers' tobacco products are absorbed by various companies. 2) The risk of wet dry climate change which makes the land submerged in water, resulting in a decrease in the quality of tobacco leaves, the risk of not getting subsidized fertilizers and fluctuating selling prices.3) There is no solution to anticipate the occurrence of crop failure, but the impact of crop failure can be minimized by providing instructions to all members of the farmer group regarding the drainage system and the application of "Curing Tunnel" technology.Keywords: Tobacco, Climate Change, Risk Management